Apical sling: an approach to posthysterectomy vault prolapse. Issue 9 (September 2016) - Alas, Alexandriah; Pereira, Ines; Chandrasekaran, Neeraja; Devakumar, Hemikaa; Espaillat, Luis; Hurtado, Eric; Davila, G.
Abstract Introduction and hypothesis This video demonstrates a transvaginal technique for vaginal vault suspension using an apical sling suspended from the sacrospinous ligaments. Methods This was a retrospective review of apical sling procedures performed from July 2013 to November 2014. The technique is started by marking the vaginal apex. A posterior dissection is performed and the sacrospinous ligaments are identified after dissection into the pararectal space. A 10-cm piece of monofilament, inelastic polypropylene tape is attached to the underside of the vaginal apex. Polypropylene sutures are placed into the sacrospinous ligament and threaded though the lateral edges of the apical sling and tied down, restoring apical support. Finally, the vaginal epithelium is closed. Results A total of 67 women underwent an apical sling procedure with 70 % (47/67) completing 6 months follow-up. The subjective cure rate ("cured" or "greatly improved") was 78.7 % and the objective cure rate (anatomical success, defined as apical prolapse stage ≤1) was 100 % (47 patients). Conclusions Our apical sling sacrospinous ligament fixation approach is a unique, minimal mesh approach using a tape commonly used for midurethral slings to suspend the vaginal apex. We achieved high anatomical success and patient satisfaction.